2014
DOI: 10.1186/1471-2369-15-82
|View full text |Cite
|
Sign up to set email alerts
|

Properdin has an ascendancy over factor H regulation in complement-mediated renal tubular damage

Abstract: BackgroundUrinary (U)-complement components have been detected in patients with proteinuric renal diseases, and complement activation via the alternative pathway (AP) is believed to play a role in renal tubular damage. The present study aimed to examine the regulation of complement AP activation in patients with renal tubular damage by focusing on the balance between properdin (P) and factor H (fH).MethodsIn the in vivo studies, U concentrations of P, fH and membrane attack complex (MAC) were measured in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Previous studies have shown an association between urinary complement proteins and tubular damage markers, including β2‐microglobulin, in IgAN as well as other types of proteinuric renal diseases . In line with this, we found significant correlations between the three complement proteins (CFH, MBL and C5b‐9) in urine and the tubular damage markers, urinary RBP and α1‐MG, both known to be ligands to the endocytic receptor megalin .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown an association between urinary complement proteins and tubular damage markers, including β2‐microglobulin, in IgAN as well as other types of proteinuric renal diseases . In line with this, we found significant correlations between the three complement proteins (CFH, MBL and C5b‐9) in urine and the tubular damage markers, urinary RBP and α1‐MG, both known to be ligands to the endocytic receptor megalin .…”
Section: Discussionsupporting
confidence: 90%
“…Zaferani and colleagues identified that tubular heparan sulphate proteoglycan (HSPG) served as a docking platform for P in proteinuric renal disease . P participation in PDP on the cell surface of PTECs enhances C3b and C5b‐9 deposition, leads to tubulointerstitial damage and worsens renal function . In connection with these evidences, serum P consumption in our patients can be explained by the deposition of P on altered renal tubules.…”
Section: Discussionsupporting
confidence: 56%
“…This situation promotes its interaction with heparan sulphate proteoglycan (HSPG) present on the extracellular matrix of PTECs, acting as a focal point for AP activation . Recent results confirmed that deposited P via HSPG on PTECs seems to be involved in complement activation, as it can increase the deposition of C3 and C5b‐9 in cellular surface in vitro . Moreover, urinary P levels were associated with higher urinary levels of soluble C5b‐9 (sC5b‐9) and with worse renal function .…”
Section: Introductionmentioning
confidence: 95%
“…Second, further studies are required to confirm and define the mechanisms underlying the absence of luminal C5b9 formation in acute PON. In this regard, the urinary excretion of C5b9 as well as other complement regulatory proteins (particularly properdin and Factor H) [29,30,59] in PON could be compared to other chronic proteinuric and nonproteinuric models of chronic kidney disease as well as different types of proteinuric diseases in humans, in future studies. Finally, the present study has only examined the acute stages of PON, and different mechanisms of C5b9mediated injury could be involved if it is combined with renal mass reduction and/or if the injections of BSA are continued for a longer duration [14] .…”
Section: Discussionmentioning
confidence: 99%